Membrane-free water filtration using inertial microfluidics - Chua, Nicholas Wei Xiong (Nanyang Technological University, 2020)
Membrane filtration is a key water treatment process to remove micron-sized particulates. However, it is prone to clogging that leads to significant pressure loss and decrease in filtration efficiency. Inertial microfluidics is an emerging membrane-free microtechnology for continuous flow size-based particle separation, but its application in water treatment remains unexplored due to insufficient throughput requirement (~ litres/min). In this work, we developed a scaled-up microfluidic device to separate large particles (~150 µm) using a high aspect ratio straight channel (millimetre sized) patterned with multiple expansion cavities along the channel sidewalls. Two channel designs with 12 and 49 expansion cavities were fabricated using stereolithography and laser cutting. We first characterized channel outlet expansion angle and observed that small expansion angle (10 degree) was optimal with minimal recirculation flow. Computational fluid dynamics (CFD) simulation and experimental characterization using 150 µm polystyrene beads were next performed to study the geometries of expansion cavities. In the 12-cavities design of wider cavity, a secondary flow consisting of a stretched vortex with its core located near to trailing edge of cavity created negative pressure to attract large particles into the cavity. In the 49-cavities design with shorter cavity width, particles also migrated toward the vortex but did not enter the cavities, resulting in significant particle enrichment next to side wall. A particle separation efficiency of 88% at ~16 mL/min (Re 350) for the centre fluid stream was achieved using a 3-outlet design. Overall, these results clearly demonstrate the feasibility of scaled-up inertial microfluidics for low cost, membrane-free particle sorting, which can be further multiplexed to achieve higher throughput for water treatment applications.